Development of an analytical method based on citric acid coated magnetite nanoparticles assisted dispersive magnetic solid-phase extraction for the enrichment and extraction of sildenafil, tadalafil, vardenafil and avanafil in human plasma and urine prior to determination by LC-MS/MS - Er, Elif Orturk; Akkaya, Erhan; Ozbek, Belma; Bakirdere, Sezgin (ELSEVIER, 2019)
A new analytical method based on dispersive magnetic solid-phase extraction (DMSPE) was introduced for the preconcentration of phosphodiesterase-5 (PDE-5) inhibitors in human urine and blood samples. For this purpose, citric acid coated magnetic iron nanoparticle was synthesized and characterized. The assay involved the extraction of sildenafil, tadalafil, vardenafil and avanafil as PDE-5 inhibitors using magnetic sorbent material. Effects of experimental variables in the extraction procedure were optimized using two techniques; one-variableat-a-time and response surface methodology. Under the optimum conditions, the limits of detection and quantification values were obtained in the range of 0.06 to 0.94 ng g(-1) and 0.19 to 3.13 ng g(-1), respectively. The proposed method showed good linearity (R-2 > 0.9968) and satisfactory repeatability (%RSD < 9.57%) even at very low concentrations. The proposed method was applied to human urine and plasma samples by spiking experiments. High percent recoveries indicated that the method is applicable for the accurate determination of selected PDE-5 analytes.
Keywords: Sildenafil; Tadalafil; Vardenafil; Avanafil; LC-QTOF-MS/MS; Preconcentration; MOLECULARLY IMPRINTED POLYMERS; FE3O4 NANOPARTICLES; BISPHENOL-A; ERECTILE DYSFUNCTION; ANALOGS; WATER; FOOD; MICROEXTRACTION; ADSORBENTS; INHIBITORS; Chemistry